Early and Long-Term Effect of Thoracic Endovascular Aortic Repair for Stanford B Aortic Dissection - Ruan, Zhong-Bao; Zhu, Li; Chen, Ge-Cai; Yin, Yi-Gang (The Thoracic and Cardiovascular Surgeon, 2015)
Background Uncomplicated Stanford B acute aortic dissection (AAD) is generally treated with medical management; whereas complicated dissections require surgery or thoracic endovascular aortic repair (TEVAR). Studies have demonstrated that long-term outcomes with medical management are suboptimal. Therefore, we sought to investigate the early and long-term clinical efficacy of TEVAR for Stanford B AAD.Materials and Methods From March 2004 to January 2008, 63 consecutive patients were treated and retrospectively placed into either one of the two groups, the TEVAR group (n = 42) and the medicine group (n = 21). All TEVAR procedures were performed in the acute phase. The changes of true and false lumen diameter were monitored with computed tomography angiography examinations in the thoracic aorta at the level of the stented segment at long-term follow-up.Results As compared with the medicine group, the age at intervention in the TEVAR group was higher (p < 0.05), and they also had more patent false lumen in this group. Patients in the TEVAR group had significantly longer hospital stays than those in the medicine group (p < 0.01). The incidence of the early events was not significantly different between the two groups. The incidence of aortic-related late events and late death were significantly higher in the medicine group than those in the TEVAR group. Log-rank tests demonstrated that patients treated with medical management had significantly more late adverse events than did those treated with TEVAR (p < 0.01). At 1-year follow-up, the true lumen diameter in the thoracic aorta at the level of the stented segment increased significantly after TEVAR, and the mean reduction of false lumen diameter was highly significant. The remodeling was stable at 3 and 5 years after TEVAR.Conclusion Patients with Stanford B AAD treated with TEVAR experienced fewer late adverse events than those treated with medical management, TEVAR could be an effective treatment for Stanford B AAD.
Keywords: aortic dissection; Stanford B; thoracic endovascular aortic repair; early events; late events